2009
DOI: 10.2298/abs0901113m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of abiotic and biotic environmental factors on weight gain of cultured carp on a carp farm

Abstract: During the period from April to October in the production season of the year 2000, seven chemical parameters of the aquatic environment were analyzed twice a month for the amount of natural food (zooplankton and bottom fauna) on pond No. 4 at the Dubica Carp Farm in Banatska Dubica (Vojvodina, Serbia). Correlation between natural food and carp growth was analyzed as well. The investigations revealed negative correlation between the amount of natural food per kilogram of ichthyomass and pH (p < 0.001, r = -0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
2
7
0
4
Order By: Relevance
“…Similar results in this country were presented by Simić (1993Simić ( , 1995, Marković (1995Marković ( , 1998, Marković and Mitrović-Tutundžić (1997), Marković et al (1998), and Paunović et al (2006a), with the highest diversity observed in submontane regions as well, but with the lowest number of species in highland areas, which was not in accordance with our results. High diversity in watercourses of over 800 m could be explained by the fact that all study sites are near-pristine to reference, which mainly refers to the Timok and Južna and Zapadna Morava river basins.…”
Section: Discussionsupporting
confidence: 74%
“…Similar results in this country were presented by Simić (1993Simić ( , 1995, Marković (1995Marković ( , 1998, Marković and Mitrović-Tutundžić (1997), Marković et al (1998), and Paunović et al (2006a), with the highest diversity observed in submontane regions as well, but with the lowest number of species in highland areas, which was not in accordance with our results. High diversity in watercourses of over 800 m could be explained by the fact that all study sites are near-pristine to reference, which mainly refers to the Timok and Južna and Zapadna Morava river basins.…”
Section: Discussionsupporting
confidence: 74%
“…Semiintensive production is based on the use of natural food from the pond environment as the main source of protein and energy, only supplemented with additional feed when the natural production in the pond is deprived (Rahman, 2006;Marković et al, 2009a). Different grains or legumes (wheat, corn, barley, triticale, soybean, sunflower) are used as added feed, as well as formulated feed of different composition and level of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…na poĉetku sezone uzgoja. U tom periodu zabeleţene su vrednosti dnevne stope rasta šarana od preko 2% što je u saglasnosti sa rezultatima koje su Marković et al (2009a) dobili prilikom istraţivanja na ribnjaku ''Dubica'' tokom sezone uzgoja 2000. godine. U proleće i poĉetkom leta tek nasaĊena riba još uvek je nenaviknuta da uzima dodatnu hranu, pa je dobar rast u ovom periodu rezultat iskorišćavanja autohtonih izvora energije i materije iz prirodne hrane u ribnjacima.…”
Section: Rast Ribeunclassified
“…Sliĉan trend porasta tvrdoće vode od poĉetka do kraja sezone uzgoja na šaranskom ribnjaku konstatuju Marković et al (2009a).…”
unclassified
See 1 more Smart Citation